First International Conference on Artificial Intelligence and Cognitive Computing AICC 2018 - Bapi, Raju Surampudi; Rao, Koppula Srinivas; Prasad, Munaga V. N. K.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents original research works by researchers, engineers and practitioners in the field of artificial intelligence and cognitive computing. The book is divided into two parts, the first of which focuses on artificial intelligence (AI), knowledge representation, planning, learning, scheduling, perception-reactive AI systems, evolutionary computing and other topics related to intelligent systems and computational intelligence. In turn, the second part focuses on cognitive computing, cognitive science and cognitive informatics. It also discusses applications of cognitive computing in medical informatics, structural health monitoring, computational intelligence, intelligent control systems, bio-informatics, smart manufacturing, smart grids, image/video processing, video analytics, medical image and signal processing, and knowledge engineering, as well as related applications.
Automatic Retail Product Image Enhancement and Background Removal -- Acquiring Best Rules that Represent Datasets -- A New Document Representation Approach for Gender Prediction using Author Profiles -- Secure Privacy Preserving of Personal Health Records using Attribute Based Encryption in Cloud Computing -- Automating WEB Interface in Relation to User Behavior -- Cognitive Based Adaptive Path Planning for Mobile Robot in Dynamic Environment -- Prediction for Indian Road Network Images Dataset Using Feature Extraction Method -- Speaker Diarization System Using Hidden Markov Toolkit -- A Generic Survey on Medical Big Data Analysis Using Internet of Things -- Smart Heart Beat Monitoring System Using Machine Learning -- Big Data Analytics on Aadhar Card Dataset in Hadoop Eco System -- A New Method for Edge Detection Under Hazy Environment in Computer Vision -- Analysis and Optimization of FIR Filters Using Parallel Processing and Pipelining.
Keywords: Computational intelligence; Artificial intelligence; Bioinformatics; Signal processing; Medical informatics; Computational Intelligence; Artificial Intelligence; Computational and Systems Biology; Signal, Speech and Image Processing; Health Informatics